2003
DOI: 10.1074/jbc.m301484200
|View full text |Cite
|
Sign up to set email alerts
|

Bruton's Tyrosine Kinase Is a Toll/Interleukin-1 Receptor Domain-binding Protein That Participates in Nuclear Factor κB Activation by Toll-like Receptor 4

Abstract: The Tec family of protein tyrosine kinases, of which Bruton's tyrosine kinase (Btk) 1 is a prototypical member, is involved in a vast array of signaling pathways in cells of hematopoietic lineage. Btk is expressed in all hematopoietic cells except T lymphocytes and natural killer cells. It is critically important for B-cell development as well as mature B-cell activation and survival. It has also been shown to be important for IgEmediated activation of mast cells resulting in allergic reactions. Btk kinase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
258
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 270 publications
(268 citation statements)
references
References 37 publications
6
258
1
3
Order By: Relevance
“…The ability of Btk to associate with the TIR domain of TLR4 was also demonstrated (10). In addition, however, we found that Btk can interact with the TIR domains of TLR8 and TLR9.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…The ability of Btk to associate with the TIR domain of TLR4 was also demonstrated (10). In addition, however, we found that Btk can interact with the TIR domains of TLR8 and TLR9.…”
mentioning
confidence: 66%
“…and TLR9-In a previous study, we found that a yeast two-hybrid screen carried out to search for possible interaction partners for Btk isolated a cDNA encoding human TLR8 (10). It was found that Btk could also interact with the TIR domains of TLR4, TLR6, and TLR9.…”
Section: Association Of Endogenous Btk With Tlr8mentioning
confidence: 99%
See 1 more Smart Citation
“…The lyn -/-btk low mice do not develop autoAb or disease but still have B cells that are hyperresponsive to BCR ligation in terms of calcium flux, MAPK activation and proliferation [48]. Btk and Lyn are both involved in proinflammatory signaling pathways downstream of the BCR and IL-5R [49][50][51][52], thus overlap in function may also occur downstream of the conserved TIR domain of TLR4, TLR6, TLR8 and TLR9, a pathway known to involve Btk [53].…”
Section: Discussionmentioning
confidence: 99%
“…Many molecules have been identified as positive or negative regulators of TLR signaling, 6,7 including phosphatases (SHP-1, SHP-2, SHIP-1, PTP1B, [8][9][10][11] etc. ), protein kinases (calmodulin-dependent protein kinase II, Btk, MEKK3, [12][13][14] etc. ), ubiquitin-related proteins (A20, Nrdp1, CHIP, [15][16][17] etc.…”
Section: Introductionmentioning
confidence: 99%